Characterization of the ultrastructure in the uterovaginal junction of the hen. (3rd May 2016) - Waqas, M. Y.; Yang, P.; Ahmed, N.; Zhang, Q.; Liu, T.; Li, Q.; Hu, L.; Hong, C.; Chen, Q.
Abstract : In poultry, the infundibulum is the place of fertilization, eggshell production, and sperm storage, while its uterovaginal junction (UVJ) is regarded as the most important site, which has abundant sperm storage tubules (SST). We examined the ultrastructure of the epithelium with relation to its unique secretory cytology in the UVJ of hens using transmission electron microscopy. The epithelium of the UVJ is lined with ciliated and secretory cells. Ciliated cells are characterized with light and dense secretory granules in supernuclear cytoplasm. Dense secretory granules in ciliated cells are larger in diameter (one μm), surrounded with a transparent rim and concentric layers, whereas the dense granules in the ciliated cells of SST are smaller (0.52 μm) in size and not surrounded by any transparent rim or layer. Ciliated cells also are involved in the shedding of exosomes and secretory vesicles in the lumen. Secretory exosomes are in close contact with cilia and directly release from the apical border into the lumen. Cell junctions are widely distributed between these cells. The secretory cells are associated with the release of secretions via apocrine blebs from microvilli and secretory vesicles, which protrude out from the surface of the epithelium. The dense secretory granules in these cells are smaller in size (0.6 μm), absent of a transparent rim or layers, and are released into the lumen through secretory vesicles. The intracellular multivesicular body (MVB) also is observed in the supernuclear cytoplasm of secretory cells, which are related to the production of exosomes. In general, the apical protrusion of the epithelium in the form of apocrine secretions, the releasing of exosomes, the identification of intracellular MVB, and the release of dense granules give the epithelium a distinct morphology in the UVJ of the hen oviduct.